Hunting in French Guiana Across Time, Space and Livelihoods - Richard-Hansen, Cecile; Davy, Damien; Longin, Guillaume; Gaillard, Laurent; Renoux, François; Grenand, Pierre; Rinaldo, Raphaëlle (Frontiers in Ecology and Evolution, 2019)
Hunting sustainability in Amazonian ecosystems is a key challenge for modern stakeholders. Predictive models have evolved from first mostly biological data-based to more recent modelling including human behavior. We analyze here the hunting data collected in French Guiana through a panel of indices aiming at drawing the puzzle of parameters influencing hunting activity and impact in various socio ecological conditions across the country. Data were collected from five different study sites differing in cultural origins and remoteness from market economy, and over a ten years period. Most indices show an impact on wildlife populations, and using a full set of indicators allowed us to better understand some underlying mechanisms that lead to a community’s hunting profile. The results showed that there are noticeable differences between the study sites in the practices and the ways hunters face the changes in environment and resources availability